PENDIDIKAN ISLAM BERKEADILAN GENDER BERBASIS MAQASHID SYARI’AH LI al-NISA’ PERSPEKTIF TRILOGI KUPI - Siti Mutholingah; Ila Fuadiyati Shova (Pascasarjana Universitas Al-Qolam Malang, 2025)
This research aims (1) to analyze how the maqashid syariah li al nisaa' approach can be used as a method for interpreting texts in efforts to protect women's educational rights and (2) find out the concept of gender-equitable Islamic education based on maqashid syariah li al nisaa with Trilogy KUPI approach. This research use literature review and the content analysis was used for the data analysis. The findings of this study are: (1) The maqashid syariah li al nisaa' approach as a method for interpreting texts to protect women's educational rights involves starting with the text, then applying it to the context, with the maqashid syariah being read through a gender perspective. (2) the concept of gender-equity Islamic education based on maqashid sharia li al nisaa with the KUPI trilogy approach, namely the concept of mubadalah in Islamic educational leadership, the concept of true justice in the accessibility of Islamic education and the concept of ma'ruf in eliminating violence against women in the process of Islamic education. Novelty in this study is the concept of gender-equitable Islamic education based on maqashid sharia li al nisaa in the perspectif of ma'ruf, mubadalah and true justice.